Pengaruh Kinerja Keuangan terhadap Nilai Perusahaan dengan Keputusan Investasi sebagai Variabel Mediasi (Studi pada Perusahaan Sektor Pertambangan yang Listing di Bursa Efek Indonesia Tahun 2012 – 2016) - Wiwik Indra Mariana; Kamaliah Kamaliah; Novita Indrawati (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2019)
The purpose of this study is to analyze the effect of financial performance (profitability, leverage, and liquidity) on investment decisions and company value, to analyze the effect of investment decisions on firm value and to analyze the effect of financial performance (profitability, leverage and liquidity) on the value of the company mediated by the decision investation. The population in this study are mining sector companies listed on the Indonesia Stock Exchange in 2012-2016. The study was conducted by collecting secondary data from the mining sector of 45 companies, the sampling method was a purposive sampling method with a sample size of 23 companies. Data analysis method uses path analysis. The results showed that financial performance as measured by leverage ratios influenced investment decisions. Financial performance as measured by the ratio of profitability and liquidity has no influence on investment decisions. Financial performance as measured by profitability and leverage ratios affect the value of the company, while financial performance as measured by liquidity ratios and investment decisions do not affect the value of the company. Financial performance measured by leverage ratio influences company value which is mediated by investment decisions. While financial performance as measured by the ratio of profitability and liquidity does not affect the value of the company mediated by investment decisions.